2018
DOI: 10.1007/s00441-018-2874-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-hexosaminidase in the male reproductive system of the lizard, Eutropis carinata. (Reptilia, Squamata) (Schneider, 1801)

Abstract: Beta-hexosaminidase (Hex) is the major lysosomal enzyme associated with the event of fertilization. In this study, we have analyzed the distribution of Hex in the testis and the epididymis of the lizard, Eutropis carinata by a polyclonal antibody of β-hexosaminidase isoform (Hex A). Presence of Hex in the epididymis was performed by Western blotting. The result reveals that Hex A is present in the epididymal epithelium, lumen as well as spermatozoa. The anatomical distribution of Hex was studied by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The studies further indicated that Hex is released from the epididymal epithelium and binds to the spermatozoa and, in the lumen, it gradually increases from the anterior to the posterior region of the epididymis. The latter report also suggested that Hex A which binds to the epididymal spermatozoa originates from the epididymis 58 . The above studies on the epididymis of E. carinata implicate that the biochemical complexity of sperm activation observed is consistent with those reported in mammals.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The studies further indicated that Hex is released from the epididymal epithelium and binds to the spermatozoa and, in the lumen, it gradually increases from the anterior to the posterior region of the epididymis. The latter report also suggested that Hex A which binds to the epididymal spermatozoa originates from the epididymis 58 . The above studies on the epididymis of E. carinata implicate that the biochemical complexity of sperm activation observed is consistent with those reported in mammals.…”
Section: Discussionmentioning
confidence: 88%
“…Beta-hexosaminidase (Hex) is the major lysosomal enzyme associated with the event of fertilization. The presence of Hex in the epididymis of the lizard E. carinata has been demonstrated 58 . The studies further indicated that Hex is released from the epididymal epithelium and binds to the spermatozoa and, in the lumen, it gradually increases from the anterior to the posterior region of the epididymis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on literatures, we proposed that a 65 kDa protein may be a lysosomal enzyme called β‐hexosaminidase secreted from epithelial cells of epididymis to bind sperm surface (Andrea et al., 2001). This enzyme has been further known to be responsible for early process of gamete interaction (Medini et al., 2018; Miranda et al., 2000). Moreover, the 70 and 73‐kDa proteins observed to be overexpressed in epididymal fluid of CS could belong to clusterin and semenogelin, respectively, as previously reported (Andrea et al., 2001; Sylvester et al., 1991).…”
Section: Discussionmentioning
confidence: 99%